Measures of Self-Perception, Level of Physical Activity, and Body Mass Index of Participants of Sports Education Camps for Youths with Visual Impairments. (January 2019) - McMahon, John; Emerson, Robert S. Wall; Ponchillia, Paul; Curtis, Amy
Introduction: This study explored the relationship between first-time or repeat participation at a sports education camp and demographic variables of gender, age, race or ethnicity, measures of self-perception, body mass index (BMI), and physical activity in participants' communities. Methods: The study was a secondary data analysis of interview and BMI data for youths with visual impairments (i.e., those who are blind or have low vision) who attended a sports education camp in one of 12 states in the years 1989, 1996, and 2000–2010. Results: The short-term intervention model of a sports education camp had a positive effect on participants' perceptions of themselves. This result was more pronounced for boys and for youths with some usable vision. Involvement in a sports education camp did not tend to translate to increased involvement in sports in a student's community. The mean BMI of first-time participants was consistent across gender, race or ethnicity, and vision category, and the BMI of first-time participants tended to be higher according to the age of the participant. Discussion: The findings revealed that the short-term intervention model of a sports education camp is highly effective in increasing self-perception for youngsters with vision impairments. Implications for practitioners: For youths with visual impairments who might be experiencing reduced social interaction, decreased self-perception or increased BMI involvement in a sports education camp is a short-term intervention that can positively impact these effects.